Peningkatan Pendapatan Keluarga Melalui UMKM Di Desa Pulung Sari Kecamatan Rantau Pulung Kabupaten Kutai Timur - Dela Nofi Anggraeni; Rita Kala Linggi; Budiman, Budiman (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
The purpose of this study was to determine and describe the increase in family income through Micro, Small and Medium Enterprises (MSMEs) in Pulung Sari Village, Rantau Pulung District, East Kutai Regency, as well as to identify the inhibiting factors in increasing family income through micro, small and medium enterprises (MSMEs) in the Village. Pulung Sari, Rantau Pulung District, East Kutai Regency. This type of research is a qualitative descriptive research. Data collection techniques were carried out by means of library research and field work with observation, interview, and documentation techniques. The results of this study indicate that increasing family income through micro, small and medium enterprises (MSMEs) in Pulung Sari Village, Rantau Pulung District, East Kutai Regency is still not optimal. needed in producing or in marketing the products of MSME actors, and there is no routine training.